Large scale patches of Calanus finmarchicus and associated hydrographic conditions off the Lofoten archipelago - Weidberg, Nicholas; Santana Hernandez, Nestor; Renner, Angelika; Falk‑Petersen, Stig; Basedow, Sünnje Linnéa (Journal of Marine Systems, 2021)
Large swarms of individuals at different spatiotemporal scales characterise the distributions of many animal species. In the ocean several mesozooplankton taxa aggregate in large patches or swarms driven by active behavioural responses to hydrographic structures, although intrinsic biotic characteristics of species´life cycles not related with the environment can also affect spatial distributions. To understand the mechanisms of aggregation and disentangle environmental and pure spatial effects contributing to patch formation, we extensively sampled a large Calanus finmarchicus patch off the Lofoten islands, northern Norway, in spring 2017 by means of Laser Optical Plankton Counter (LOPC) cross shelf transects and biophysical samplings at fixed stations. We observed a clear association between the buoyant layer of the fresh, cold Norwegian Coastal Current (NCC) and high surface copepod abundances. Off shelf lateral displacements of the NCC along its path may retain copepods from the offshore basins. At deeper layers, copepod abundances increased markedly at regions with low sea level anomalies and reduced vertical flows. Our results also suggest that copepods performed short range diel vertical migration within the patch. Potential future changes in the seasonality and structure of the NCC and their impact on swarm occurrence and formation are discussed.